2015
DOI: 10.1098/rsif.2014.1080
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale modelling of the dynamics of cell colonies: insights into cell-adhesion forces and cancer invasion from in silico simulations

Abstract: Studying the biophysical interactions between cells is crucial to understanding how normal tissue develops, how it is structured and also when malfunctions occur. Traditional experiments try to infer events at the tissue level after observing the behaviour of and interactions between individual cells. This approach assumes that cells behave in the same biophysical manner in isolated experiments as they do within colonies and tissues. In this paper, we develop a multi-scale multi-compartment mathematical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Consistent with computational simulations demonstrating that the rate of adherens junction turnover can be a major determinant of colony growth53, we found that impairment of adherens junction homoeostasis by inhibition of Rho GTPase signalling54 with the Rho kinase (ROCK) inhibitor Y-27632 promoted colony expansion (Fig. 7b,c).…”
Section: Resultssupporting
confidence: 87%
“…Consistent with computational simulations demonstrating that the rate of adherens junction turnover can be a major determinant of colony growth53, we found that impairment of adherens junction homoeostasis by inhibition of Rho GTPase signalling54 with the Rho kinase (ROCK) inhibitor Y-27632 promoted colony expansion (Fig. 7b,c).…”
Section: Resultssupporting
confidence: 87%
“…For example, Bambardekar et al proposed and validated a continuum viscoelastic constitutive equation to describe the force dynamics at epithelial cell–cell adhesions, while Coburn et al used a particle‐based method, known as the vertex‐based method, to simulate the acto‐myosin contractile forces that transmit across the tissue through the cell–cell adhesions. Tightly coupled with experimental data, these models have helped to estimate tensions at the cell–cell adhesion interface and could therefore be adopted for studies on the role of cell–cell adhesions on single‐cell mechanobiology. Thanks to these many advances in measuring and modeling cell–cell adhesions and their acto‐myosin generated forces, research in this field is now focused on uncovering how these mechanical forces regulate cellular and tissue remodeling.…”
Section: Measurements and Models Of The Contribution Of Adhesions Andmentioning
confidence: 99%
“…Regarding cancer initiation, growth and invasion of cancer cells, and the use of cell-based modelling, we refer to the studies by Schlüter et al. (2014) and Vermolen et al. (2015).…”
Section: Introductionmentioning
confidence: 96%